World Bank Group Macroeconomic Models for Climate Policy Analysis - World Bank (World Bank, Washington, DC, 2022)
Policymakers in developing countries face multiple challenges related to climate change. To provide policymakers with reliable recommendations on a variety of climate related policies, the WBG has a diverse and complementary set of models. The analytics range from evaluating the aggregate, sectoral, and welfare effects of mitigation measures to assessing country-specific adaptation needs, considering the impacts of extreme weather events as well as gradual global warming. Key indicators include macroeconomic outcomes, sectoral indicators, co-benefits and poverty and distributional issues. This report summarizes the range of climate and development issues addressed by each model in the WBG suite, revealing both strengths and limitations of individual models, as well as the complementarity among models.